Exploring the in situ evolution of nitrofurantoin resistance in clinically derived uropathogenic Escherichia coli isolates. (8th December 2022) - Vallée, Maxime; Harding, Chris; Hall, Judith; Aldridge, Phillip D; TAN, Aaron
Abstract: Background: Nitrofurantoin has been re-introduced as a first-choice antibiotic to treat uncomplicated acute urinary tract infections in England and Wales. Highly effective against common uropathogens such as Escherichia coli, its use is accompanied by a low incidence (<10%) of antimicrobial resistance. Resistance to nitrofurantoin is predominantly via the acquisition of loss-of-function, step-wise mutations in the nitroreductase genes nfsA and nfsB . Objective: To explore the in situ evolution of Nit R in E. coli isolates from 17 patients participating in AnTIC, a 12-month open label randomized controlled trial assessing the efficacy of antibiotic prophylaxis in reducing urinary tract infections (UTIs) incidence in clean intermittent self-catheterizing patients. Methods: The investigation of Nit R evolution in E. coli used general microbiology techniques and genetics to model known Nit R mutations in Nit S E. coli strains. Results: Growth rate analysis identified a 2%–10% slower doubling time for nitrofurantoin resistant strains: Nit S : 20.8 ± 0.7 min compared to Nit R : 23 ± 0.8 min. Statistically, these data indicated no fitness advantage of evolved strains compared to the sensitive predecessor ( P -value = 0.13). Genetic manipulation of E. coli to mimic Nit R evolution, supported no fitness advantage ( P -value = 0.22). In contrast, data argued that a first-step mutant gained a selective advantage, at sub-MIC (4–8 mg/L) nitrofurantoin concentrations. Conclusion: Correlation of these findings to nitrofurantoin pharmacokinetic data suggests that the low incidence of E. coli Nit R, within the community, is driven by urine-based nitrofurantoin concentrations that selectively inhibit the growth of E. coli strains carrying the key first-step loss-of-function mutation.